Nutritional evaluation and potential of locally available alternative feed resources for sustainable poultry production: a case study of smallholder farms in central and Southern Ethiopia - Getahun, A.; Kechero, Y.; Yemane, N.; Dessie, Tadelle; Esatu, Wondmeneh (2025)
Poultry farming plays a vital role in the livelihoods of smallholder farmers in central and southern Ethiopia by providing protein and income. However, the high cost of conventional feeds has created a need for alternative feed ingredients. This study identifies and assesses the nutritional value of locally available alternative feed resources for poultry in the region. Data were collected from 360 households across the Hadiya, Wolaita, and Gamo zones to examine household demographic and socio-economic characteristics, feeding practices, and the use of alternative feeds such as enset (Ensete ventricosum) corm, avocado (Persea americana) seed kernel, mango (Mangifera indica) seed kernel, and moringa (Moringa stenopetala) leaf meal. A multistage sampling technique and field measurements were employed for data collection. The common alternative feeds were sampled and analysed for their nutritional characteristics. The majority of households (80%, N = 288) engaged in supplementary feeding, primarily using cereal grains. Nutritional evaluations revealed significant differences in nutrient content: moringa leaf meal had the highest crude protein (CP, 30.8 ± 0.35%), while mango seed kernel had the highest carbohydrate content (79.62%). An average, alternative feeds had higher crude protein content (P < 0.05) than conventional feeds such as maize (8.5% CP) but lower than soybean meal (40.1% CP). Among the alternative feed resources, avocado seed kernel contained 4185.97 ± 43.37 Kcal ME/kg DM, mango seed kernel 3755.48 ± 32.3 Kcal ME/kg DM, and enset corm 3611.16 ± 5.04 Kcal ME/kg DM, showing comparability with conventional feeds. Alternative feeds generally exhibited higher carbohydrate levels (p < 0.05) and comparable essential nutrient contents, demonstrating their potential as poultry diet supplements. Some alternative feed ingredients contained anti-nutritional factors like tannins (mean = 2.3%) and oxalates (mean = 1.1%), but their harmful effects could be eliminated through proper processing. This underscores the importance of processing to minimize adverse effects. The findings highlight the potential of local feed resources to reduce reliance on expensive conventional feeds and support sustainable poultry production.